Minimum Wage Rates and the Pure Theory of International Trade - Brecher, Richard A. (Quarterly Journal of Economics, 1974)
Introduction, 98. — I. The minimum-wage economy, 99. — II. International equilibrium, 109. — III. Summary, 115.